The development of a new accountability measurement framework and tool for global health initiatives. Issue 7 (3rd June 2020) - Martin Hilber, Adriane; Doherty, Patricia; Nove, Andrea; Cullen, Rachel; Segun, Tunde; Bandali, Sarah
Abstract: The Global Strategy for Women's Children's and Adolescents' Health emphasizes accountability as essential to ensure that decision-makers have the information required to meet the health needs of their populations and stresses the importance of tracking resources, results, and rights to see 'what works, what needs improvement and what requires increased attention'. However, results from accountability initiatives are mixed and there is a lack of broadly applicable, validated tools for planning, monitoring and evaluating accountability interventions. This article documents an effort to transform accountability markers—including political will, leadership and the monitor–review–act cycle—into a measurement tool that can be used prospectively or retrospectively to plan, monitor and evaluate accountability initiatives. It describes the development process behind the tool including the literature review, framework development and subsequent building of the measurement tool itself. It also examines feedback on the tool from a panel of global experts and the results of a pilot test conducted in Bauchi and Gombe states in Nigeria. The results demonstrate that the tool is an effective aid for accountability initiatives to reflect on their own progress and provides a useful structure for future planning, monitoring and evaluation. The tool can be applied and adapted to other accountability mechanisms working in global health.